Ageing oil well integrity assessment and rehabilitation / Ramesh Ramasamy - Ramesh , Ramasamy (2018)
Majority of the prominent oilfields around the world are becoming mature, with their wells exceeding 30-40 years, and in some cases, even up to 50 years. The common dilemma faced by the operators worldwide dealing with these ageing fields spanning across the North Sea, Middle East and Southeast Asia are ways to deal with the associated ageing assets, particularly the well structural barriers. The deteriorations on these structures, consisting of corrosion, cement shortfall, loss of centralization and other structural defects, in addition to the increased operating demands are pushing the structures beyond their allowable limits to handle the excessive loads, hence creating larger risk profile for the operators to deal with. This thesis is primarily aimed to provide substantial contribution to identifying and highlighting some of the key well integrity challenges, uncertainties and present validated methods to address these issues. This thesis is also a synthesis of work from a broad range of studies pertaining to well integrity, encompassing various individual aspects of ageing related degradations, specialized inspections, structural assessments and rehabilitation works. The deterministic global structural assessments are proposed for the as-built conditions, and relevant corrosion measurements will enable the in-place evaluations to be carried out. This is followed by development of a prioritization criteria for categorizing the more critical wells urgently requiring repairs. This group is further streamlined by more advanced inspections to quantify some of the uncertainties involving the downhole conditions and remaining annular cement bond with the development of a conductor/casing preload inspection tool based on the ultrasonic longitudinal critically refracted wave. The use of probabilistic methods on structural reliability is also proposed using the first-order method and computer-based Monte-Carlo and Bootstrap algorithms to address the uncertainties associated with the ageing wells. A coherent decision-making methodology is developed and presented in this thesis to further consolidate the repairs/rehabilitations planning of the selected wells. Finally, the structural repair designs are proposed based on existing concepts involving welding, and more economical techniques involving clamping and grouting to provide load mitigations on the existing well structures for continued extended life. Application of the analyses and monitoring methods proposed in this thesis is applied onto a group of 40-50 years old water injection and production wells from a shallow-water high-salinity brownfield. Conclusions can be drawn from the structural assessments and monitoring techniques proposed in this thesis, that the successful life extensions of ageing wells are completely feasible and can be systematically carried out very effectively, and at an optimal cost within the limitations stipulated in this work.